Failure to activate the IFN-β promoter by a paramyxovirus lacking an interferon antagonist() - Killip, M.J. (Academic Press, 2011)
It is generally thought that pathogen-associated molecular patterns (PAMPs) responsible for triggering interferon (IFN) induction are produced during virus replication and, to limit the activation of the IFN response by these PAMPs, viruses encode antagonists of IFN induction. Here we have studied the induction of IFN by parainfluenza virus type 5 (PIV5) at the single-cell level, using a cell line expressing GFP under the control of the IFN-β promoter. We demonstrate that a recombinant PIV5 (termed PIV5-VΔC) that lacks a functional V protein (the viral IFN antagonist) does not activate the IFN-β promoter in the majority of infected cells. We conclude that viral PAMPs capable of activating the IFN induction cascade are not produced or exposed during the normal replication cycle of PIV5, and suggest instead that defective viruses are primarily responsible for inducing IFN during PIV5 infection in this system.